Magelang City Legal Administration Data Archived Based on Document Tagging: Proposed Concept - Safin, Fatih Ali; Primadewi, Ardhin; Arumi, Endah Ratna (Universitas Muhammadiyah Yogyakarta, 2024)
The Office of the Legal Section of the Regional Government Secretariat of the City of Magelang (SETDA of Magelang City) currently uses traditional data archiving. Research at the SETDA of Magelang City shows that the processing of records, incoming and outgoing documents is still done manually in a special recording book. The impact is duplicated documents, this is an employee's negligence in filing large numbers of documents. Documents archived at the SETDA of Magelang City are still stored in printed form and stored in a work cupboard. The management of these documents has weaknesses, namely the arrangement of documents is carried out neatly but many documents are not recorded and lost. This situation causes the employees of the SETDA of Magelang City to have difficulty managing the documents that have been received. This study uses 4 stages. These stages include problem identification, literature study, observation and interviews, system design. Efforts to solve this problem will focus on creating a data archiving application system to make it easier for SETDA employees in Magelang City to search for historical data or data that is being worked on. This application will carry the concept of document tagging which is expected to help manage documents and ensure the security of documents. Document Tagging as a process of marking a document with relevant information attached to the document. Research will develop a prototype data archiving system and focus on special tag types in documents to indicate the type of documents in the application. The results obtained from this research are to assist Regional Secretariat employees in managing the filing of letters which were previously manual, now digital by using an administrative data archiving system and making it easier to search for data based on tagging.